Reading and writing - Practical Tools. - Leite, Isabel (2019)
Researchers have made a lot of progress in determining how children learn to read/write. Yet, there is still a gap between current scientific knowledge and public understanding. Knowledge from diverse fields is rapidly expanding; information is disperse; theoretical models, concepts and data are not always easy to interpret; and some scientific findings are not even brought to teachers attention. Reading and Writing - Pratical Tools is a project that aims to close the gap between what we know and what we do. A group of researchers is reexamining the science to distill the most important messages and to present them in a way that teachers will find most helpful. A comprehensive Web site is being developed, with detailed information on research-based principles for teaching reading/writing, a glossary of scientific terms and a list of evidence-based resources. The aim is to guide teachers to make teaching more effective.